(untitled) (Geographical Journal of Nepal, 2018)
This paper discusses the causes and consequences of agricultural land fragmentation in Nawalparasi district. Primary and secondary sources of information at District and Village Development Committees (Now Municipalities and Rural Municipalities) levels are used. A total of 93 households were interviewed in three VDCs from Nawalparasi district of Nepal. Socio-economic, legal and infrastructure development factors are responsible for fragmentation of agricultural land. Results showed that there has been decreasing productivity of land due to fragmentation of agricultural land. It is mainly due to increasing time of labor input, less opportunity of using modern chemical fertilizer on the one hand and the problem in using modern agricultural equipment such as tractors on the other. The Geographical Journal of Nepal Vol. 11: 95-112, 2018